2022
DOI: 10.1002/pro.4474
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the allosteric response of the PICK1 PDZ domain to different ligands with all‐atom simulations

Abstract: The PDZ family is comprised of small modular domains that play critical roles in the allosteric modulation of many cellular signaling processes by binding to the C‐terminal tail of different proteins. As dominant modular proteins that interact with a diverse set of peptides, it is of particular interest to explore how different binding partners induce different allosteric effects on the same PDZ domain. Because the PICK1 PDZ domain can bind different types of ligands, it is an ideal test case to answer this qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 94 publications
0
9
0
Order By: Relevance
“…We found that the covid-19 S protein shows the expected high correlation between the occurrence of mutations and site flexibility (Figure 3) when we compare %DFI (DFI ranked by percentile) to the average number of variants per position found within a given %DFI bin. Previous studies have indicated that rigid residues are critical for functional dynamics, thus more likely to impact function if mutated and, generally, can lead to a loss of function and thus more conserved (Kim, H. et al 2015; Butler et al 2018; Modi, Risso, et al 2021; Modi, Campitelli, et al 2021; Kazan et al 2022; Ose, Butler, et al 2022; Stevens et al 2022; Campitelli et al 2020a; Kumar, A., Glembo, T.J., Ozkan, S.B. 2015b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the covid-19 S protein shows the expected high correlation between the occurrence of mutations and site flexibility (Figure 3) when we compare %DFI (DFI ranked by percentile) to the average number of variants per position found within a given %DFI bin. Previous studies have indicated that rigid residues are critical for functional dynamics, thus more likely to impact function if mutated and, generally, can lead to a loss of function and thus more conserved (Kim, H. et al 2015; Butler et al 2018; Modi, Risso, et al 2021; Modi, Campitelli, et al 2021; Kazan et al 2022; Ose, Butler, et al 2022; Stevens et al 2022; Campitelli et al 2020a; Kumar, A., Glembo, T.J., Ozkan, S.B. 2015b).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have indicated that rigid residues are critical for functional dynamics, thus more likely to impact function if mutated and, generally, can lead to a loss of function and thus more conserved (Kim, H. et al 2015;Butler et al 2018;Modi, Risso, et al 2021;Modi, Campitelli, et al 2021;Kazan et al 2022;Ose, Butler, et al 2022;Stevens et al 2022;Campitelli et al 2020a;Kumar, A., Glembo, T.J., Ozkan, S.B. 2015b).…”
Section: Asymmetry In Communications Among the Network Of Interaction...mentioning
confidence: 99%
“…Our DFI metric calculates the relative flexibility/rigidity of individual residues in an protein (Campitelli et al, 2020; Kumar et al, 2015; Larrimore et al, 2017; Modi, Risso, et al, 2021; Stevens et al, 2022). The DFI algorithm, which is developed using linear response theory and perturbation response scanning, calculates the average response of a residue as a result of a perturbation on every other residue in a protein (Gerek & Ozkan, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Dynamic flexibility index (Butler et al, 2018; Gerek & Ozkan, 2011; Kazan et al, 2022; Kumar et al, 2015; Larrimore et al, 2017; Modi, Risso, et al, 2021; Ose et al, 2022; Stevens et al, 2022) uses the PRS technique that combines Elastic Network Model (ENM) and Linear Response Theory (LRT) (Nevin Gerek et al, 2013). In PRS, Brownian‐like unit forces F are applied sequentially to each residue as perturbations (Atilgan et al, 2010; Kumar et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…We prepared the time series %DFI by averaging 3 adjacent time windows, respectively (0.5 μs-1 μs, 1 μs-1.5 μs, and 1.5 μs-2 μs). As our earlier works (Butler et al, 2015;Kazan et al, 2022;Larrimore et al, 2017;Modi, Campitelli, et al, 2021) highlight that the DFI profiles capture the related function (Butler et al, 2018;Campitelli et al, 2021;Kolbabakartchner et al, 2021;Modi, Risso, et al, 2021;Ose et al, 2022;Stevens et al, 2022;Zou et al, 2015), we cluster these time series of the DFI values of each variant using PCA (see Section 3.4) to compare their dynamics profiles. The first two principal components are responsible for most of the variance in the mutant DFI profiles.…”
Section: Binding To Group I Peptidementioning
confidence: 99%